2009
DOI: 10.3109/09638280903304490
|View full text |Cite
|
Sign up to set email alerts
|

Perceived spasticity in chronic spinal cord injured patients: Associations with psychological factors

Abstract: Perceived spasticity appeared associated with psychological factors in complete patients with SCI: Those with higher levels of reassuring thoughts and lower levels of helplessness reported relatively lower levels of perceived spasticity. Large prospective cohort studies are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…19 As the focus of this paper is on psychosocial issues, papers on relationships between SWB and disablement factors, 14 secondary condition, 20 and environmental factors, 21 except for social support, 19,22 have been excluded, as well as papers on the importance of psychosocial factors as predictors of functional outcomes, 23 pain 24 and other secondary conditions. 25,26 RESULTS Life satisfaction of people with SCI Mean life satisfaction scores are instrument dependent and need a reference to reveal meaningful information. Several studies have compared life satisfaction of people with long-standing SCI with that of the general population (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…19 As the focus of this paper is on psychosocial issues, papers on relationships between SWB and disablement factors, 14 secondary condition, 20 and environmental factors, 21 except for social support, 19,22 have been excluded, as well as papers on the importance of psychosocial factors as predictors of functional outcomes, 23 pain 24 and other secondary conditions. 25,26 RESULTS Life satisfaction of people with SCI Mean life satisfaction scores are instrument dependent and need a reference to reveal meaningful information. Several studies have compared life satisfaction of people with long-standing SCI with that of the general population (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, patients who report high levels of helplessness and low levels of acceptance with regard to their illness, emphasize the negative aspects of their condition. They generalize their illness cognitions, defined as cognitive reactions to an uncontrollable, long-term stressor of coping with and adjusting to a chronic condition [16], to all facets of daily life and consequently experience worse physical and psychological functioning [16-19]. In this view, illness cognitions (IC) can be considered as prognostic factors predicting physical functioning, psychological distress and therefore possibly adaption to society.…”
Section: Introductionmentioning
confidence: 99%
“…56 However, the presence of spasticity may be a disturbance if there is a high degree of pain, a high disturbance in day-to-day activities, less range of motion, more contractures, or more complications and hospitalizations. 1, 78 …”
Section: Introductionmentioning
confidence: 99%
“…9 It has been shown that the severity of the spasticity is correlated to many psychological factors. 7 One study suggested there was a relationship between ‘reassuring thoughts’ and less spasticity. 7 Conversely, excitable emotions, including anxiety, could trigger spasms.…”
Section: Introductionmentioning
confidence: 99%